Erratum: Barriers to Sustaining Dog Vaccination Campaigns against Rabies: Perspectives from Dog and Cat Owners and Other Stakeholders in Kisarawe District, Tanzania (Tanzania Medical Journal, 2025)
ErratumThe original version of this article (1) unfortunately contained two mistakes.Author, “Fasina O. Folorunso” is not affiliated with “Food and Agriculture Organization of the United Nations, Lusaka, Zambia” and never has been. Correct affiliations are as provided below.In addition, the article text contained errors in the abstract and PDF version.  The text “It causes a loss of 3.7 million Disability Adjusted Years (DALYs) per year and about 8.6 billion USD of economic losses” under the abstract should correctly read as "It causes a loss of 3.7 million disability-adjusted life years (DALYs) and about 8.6 billion USD of economic losses per year".